New data on the morphology and taxonomy of some spiruridan nematodes (Spirurida) parasitising fishes in Jammu and Kashmir, India - Moravec, Frantisek; Chaudhary, Anshu; Ahmed, Mumtaz; Shanker Singh, Hridaya (Folia parasitologica, 2022)
Adult specimens of five little-known species of spiruridan nematodes (Spirurida) were collected during occasional examinations of some fishes from the Poonch River in Jammu and Kashmir, India: Procamallanus (Spirocamallanus) bilaspurensis Gupta et Duggal, 1973 in Mastacembelus armatus (Lacépède) (Mastacembelidae, Synbranchiformes), Rhabdochona (Rhabdochona) indica Moravec, Scholz, Ash et Kar, 2010 in Crossocheilus latius (Hamilton) (Cyprinidae, Cypriniformes), Rhabdochona (Rhabdochona) turkestanica (Skryabin, 1917) in Schizothorax richardsonii (Gray) (Cyprinidae, Cypriniformes) and both Rhabdochona (Rhabdochona) hospeti Thapar, 1950 and Rhabdochona (Globochona) cf. chodukini Osmanov, 1957 in Tor putitora (Hamilton) (Cyprinidae, Cypriniformes); besides these, unidentifiable physalopterid larvae were recorded from M. armatus and T. putitora. Their detailed light and electron microscopical studies revealed some taxonomically important, previously not observed features and made possible their redescription. Fourth-stage larvae of P. (S.) bilaspurensis and R. (R.) turkestanica are described for the first time. The latter is resurrected as an independent species. The following are considered to be species inquirendae: a total of nine poorly described species of Rhabdochona Railliet, 1916 from T. putitora in Balochistan, Pakistan, all listed in the monograph of Kakar et al. (2011), plus an additional 15 species of the genus reported from cyprinids and a catfish in the same region (Balochistan) by the same authors. Also three congeneric species from India (R. nemacheili Rautela et Malhotra, 1982, R. putitora Kaur et Khera, 1991 and R. tori Gupta et Srivastava, 1982) and one from Pakistan (R. charsaddiensis Siddiqi et Khattak, 1984) should be considered as species inquirendae due to their poor descriptions. The names of Rhabdochona putitori Anjum, 2013, R. indusi Soofi, Birmani et Dharejo, 2017 and R. sindhicus Soofi, Birmani, Dharejo, Abbasi et Ghachal, 2020 are invalid according to the International Code of Zoological Nomenclature.
Keywords: Animals; Physalopteridae; Nematoda; Parasitic nematode; India; Cyprinidae; nemoci ryb; Fish Diseases; Fishes; Rhabdochonidae; ryby; Camallanidae; hlístice; Poonch River; Spirurida; Procamallanus; zvířata; Rhabdochona; Indie; South Asia; freshwater fish